Phytoplankton Community Structure in the Intensive Cultivation System of Pacific White Shrimp (Litopenaeus vannamei) in Situbondo, East Java - Maulidhya, Shania; Latuconsina, Husain; Prasetyo, Hamdani Dwi (Agrikan Jurnal Agribisnis Perikanan, 2024)
Phytoplankton has been known to play its role as an indicator of water quality. In the intensive cultivation system of Pacific White Shrimp (Litopenaeus vannamei), phytoplankton can respond to water quality dynamics simultaneously. However, the impact of weather differences on community structure and phytoplankton diversity has not been further investigated. Here we analyze water quality and phytoplankton diversity in ponds, including uniformity and dominance. The results showed that 12 genera of phytoplankton were found in sunny weather, whereas 9 genera were found in rainy weather. Phytoplankton diversity in sunny weather is greater. The diversity index (H') value when it rains and shines is in the medium category with a stable community structure and low polluted water conditions. The uniformity value (E') is moderate. No plankton dominance was found (C â‰¤ 0.5) with the highest important index value during rain being Rhizosolenia sp. and Chlorella sp. when it's sunny. Water quality in general does not differ and meets quality standards except for the nitrate and phosphate values. Nitrate and phosphate values in both weather conditions exceeded standard standards. Differences in the types of phytoplankton present in different weather can be caused by the brightness that enters the water. Apart from that, the volume of water and the dilution and mixing effect of rainwater can cause differences in the amount. The source of growth nutrients is a supporting factor for phytoplankton growth.